Cabergoline for Cushing's disease: a large retrospective multicenter study. Issue 3 (March 2017) - Ferriere, A; Cortet, C; Chanson, P; Delemer, B; Caron, P; Chabre, O; Reznik, Y; Bertherat, J; Rohmer, V; Briet, C; Raingeard, I; Castinetti, F; et al.
Abstract : Objective: The efficacy of cabergoline in Cushing's disease (CD) is controversial. The aim of this study was to assess the efficacy and tolerability of cabergoline in a large contemporary cohort of patients with CD. Design: We conducted a retrospective multicenter study from thirteen French and Belgian university hospitals. Methods: Sixty-two patients with CD received cabergoline monotherapy or add-on therapy. Symptom score, biological markers of hypercortisolism and adverse effects were recorded. Results: Twenty-one (40%) of 53 patients who received cabergoline monotherapy had normal urinary free cortisol (UFC) values within 12 months (complete responders), and five of these patients developed corticotropic insufficiency. The fall in UFC was associated with significant reductions in midnight cortisol and plasma ACTH, and with clinical improvement. Compared to other patients, complete responders had similar median baseline UFC (2.0 vs 2.5xULN) and plasma prolactin concentrations but received lower doses of cabergoline (1.5 vs 3.5 mg/week, P <  0.05). During long-term treatment (>12 months), cabergoline was withdrawn in 28% of complete responders because of treatment escape or intolerance. Overall, sustained control of hypercortisolism was obtained in 23% of patients for 32.5 months (19–105). Nine patients on steroidogenesis inhibitors received cabergoline add-on therapy for 19 months (1–240). Hypercortisolism was controlled in 56% of these patients during the first year of treatment with cabergoline at 1.0 mg/week (0.5–3.5). Conclusions: About 20–25% of CD patients are good responders to cabergoline therapy allowing long-term control of hypercortisolism at relatively low dosages and with acceptable tolerability. No single parameter, including the baseline UFC and prolactin levels, predicted the response to cabergoline.